Using LoRaWAN smart city infrastructure as backup network for Industry 4.0 enabled vehicles - Ferrari, Paolo; Sisinni, Emiliano; Fernandes Carvalho, Diego; Signoretti, Gabriel; Silva, Marianne; Silva, Ivanovitch; Silva, Diego (Anais Estendidos do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2019)
Intelligent vehicles are the very next future of the automotive sector, which is renewing itself following Industry 4.0 paradigms. Today, car manufacturers are rapidly increasing the number of vehicles that continuously transmit data to the Internet, in order to enable the virtuous feedback paths foreseen by Industry 4.0. Such data are used to improve production (and products) during the entire lifetime of plants (and cars, also). A data link between on board devices and Internet must be created. Currently, the OBD (On Board Diagnostic) interface is available in the majority of cars and trucks. Some Edge devices with OBD and 3G/4G modems have been created, enabling easy Internet connection. However, congestion situation, as well as temporary outages, may create significant holes in the 3G/4G coverage. Recently, the transformation of city into Smart City is begun. An impressive number of new sensors are deployed in urban area. New wireless technologies are on the rise and, among them, LoRaWAN is the most used. If a vehicle is considered like a mobile sensor, then a viable option to fill 3G/4G gaps is the use of LoRaWAN infrastructure inside a Smart City. This paper deals with the creation of the prototype of an embedded platform which includes both OBD-II interface, 3G/4G connectivity and also LoRaWAN for backup situation. Considering the Smart City use cases, the application constrains regarding intelligent vehicles are discussed in order highlight design directions for the correct integration with the LoRaWAN infrastructure.